Crystal structure of methyl 2,7,7-trimethyl-4-(3-methylthiophen-2-yl)-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate, C19H23NO3S - Lu Xiao-Qing; Zhang Huan-Hu; Yang Rui; Zhu Si-Yuan; Wang Fu-Sheng (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C19H23NO3S, monoclinic, P21/n (no. 14), a = 9.0403(15) Å, b = 18.213(3) Å, c = 11.1889(19) Å, β = 107.964(2)°, V = 1752.4(5) Å3, Z = 4, Rgt(F) = 0.0498, wRref(F2) = 0.1536, T = 296(2) K.